2020
DOI: 10.3390/plants9091075
|View full text |Cite
|
Sign up to set email alerts
|

Turkish Propolis and Its Nano Form Can Ameliorate the Side Effects of Cisplatin, Which Is a Widely Used Drug in the Treatment of Cancer

Abstract: This study was performed to determine the effects of chitosan-coated nano-propolis (NP), which is synthesized via a green sonochemical method, and propolis on the side effects of cisplatin (CP), which is a widely used drug in the treatment of cancer. For this aim, 56 rats were divided into seven groups, balancing their body weights (BW). The study was designed as Control, CP (3 mg/kg BW at single dose of CP as intraperitoneal, ip), Propolis (100 mg/kg BW per day of propolis by gavage), NP-10 (10 mg/kg BW of NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 78 publications
(89 reference statements)
0
7
1
Order By: Relevance
“…Although in vivo assays have demonstrated the efficacy of nanoparticles containing propolis (Seven et al, 2020), in our study, the extract exhibited a higher immunomodulatory activity than nanoparticles regarding cytokine production by immune cells in vitro. Since the efficiency of nanoparticles encapsulation was almost 100%, one may speculate that propolis constituents were not released within the incubation period or that nanoparticles could be mostly internalized without releasing propolis constituents in the supernatant to further act in cell membrane receptors.…”
contrasting
confidence: 66%
“…Although in vivo assays have demonstrated the efficacy of nanoparticles containing propolis (Seven et al, 2020), in our study, the extract exhibited a higher immunomodulatory activity than nanoparticles regarding cytokine production by immune cells in vitro. Since the efficiency of nanoparticles encapsulation was almost 100%, one may speculate that propolis constituents were not released within the incubation period or that nanoparticles could be mostly internalized without releasing propolis constituents in the supernatant to further act in cell membrane receptors.…”
contrasting
confidence: 66%
“…It was demonstrated that CA maintains the structural integrity of the membranes against alcohol-intoxication, 70 and protects the liver from cadmium toxicity in rats, 71 which is in line with previous findings demonstrated that chitosan-coated nano-propolis protects liver and kidney against cisplatin toxicity in rats, and that nano-propolis was more effective than propolis and had the potential to ameliorate cisplatin negative effects, while overcoming serious side effects such as liver and kidney damage. 72 The solid EC-bearing mice exposed to γ-irradiation displayed a slight considerable rise of serum urea level, while treatment of solid EC-bearing mice with ZnO-CA NPs, alone or combined with γ-radiation, exhibited a considerable increase in serum urea level compared to untreated solid EC-bearing mice. The increased serum urea could be attributed to enhanced protein breakdown after exposure to ionizing radiation, where the end product of protein catabolism is urea.…”
Section: Discussionmentioning
confidence: 92%
“…This is due to the properties of chitosan, which has a wide range of biological activities, such as non-toxic, biodegradable, antibacterial activity, wound healing and biocompatibility, which can be combined with polymers, metals, and ceramic materials. It is also employed for material-body contact because the free amino groups in cationic charge promote interaction with the anionic cell surface [ 96 , 97 ]. PVA is a water-soluble polymer that is also biocompatible, biodegradable, and capable of enhancing oxygen permeability.…”
Section: Current Nanoformulations Of Propolismentioning
confidence: 99%
“…Nanopropolis has been widely reported for its use as a cancer therapy. A previous study reported that nanopropolis has efficacy in ameliorating severe hepatotoxicity and nephrotoxicity caused by drugs at a dose of 30 mg/kg [ 96 ]. In addition, other research suggests that nanopropolis exerts a notable inhibitory influence on tumor development in female mice.…”
Section: Pharmacological Actions Of Nanopropolis In Various Diseases ...mentioning
confidence: 99%